TRANSLATION PROCEDURES OF TOURISM TERMINOLOGY IN DIGITAL TOURISM EDUCATION - Naiza Gadiza; Zainuddin Hasibuan; Ulfa Mahira; Hurriyatul Assyifa; Zibran Malaci (Merwin Publisher, 2026)
Tourism terminology carries specific sociocultural and operational concepts, requiring precise translation procedures to prevent communication gaps in digital media. While previous studies focus heavily on printed tourism brochures or websites, research addressing translation procedures in digital audiovisual educational content remains scarce. This descriptive qualitative study analyzes the translation procedures applied to technical tourism terms from Indonesian into English in a YouTube instructional video on Guru Dane’s channel. Data were sourced from the video transcript containing fifteen specialized tourism terms and analyzed based on Pinchuck’s (1977) and Newmark’s (1988) frameworks. The analysis reveals 18 operational applications of translation procedures: literal translation (8 applications; 44.4%), borrowing (4 applications; 22.2%), adaptation (4 applications; 22.2%), and modulation (2 applications; 11.1%). The findings highlight the strategic use of couplets combining two distinct procedures to bridge cultural registers. Literal translation dominates because translating foundational tourism terms in digital platforms prioritizes direct conceptual correspondence to deliver professionally acceptable technical messages. Theoretically, this study enriches register analysis in audiovisual translation. Practically, it provides a linguistic reference for educators and digital content creators in developing accurate bilingual learning materials.